PENGARUH SENAM ERGONOMIS TERHADAP PERUBAHAN KADAR ASAM URAT PADA PENDERITA ASAM URAT - Ria Sugesti; Dahrizal Dahrizal; Erni Buston (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract : Uric acid disease occurs due to the buildup of uric acid in the body. One of its causes is due to lack of physical activity which make the transport of residual burning (uric acid) in the body becomes disturbed. The objective of this research was to find out the effect of ergonomic gymnastic toward the changes of uric acid level on patients of uric acid in community health center of Lingkar Timur Bengkulu city. The design of this research was quasi experimental with pre and post test with control group design. The samples consisted of 26 respondents. There were 13 respondents of intervention group and 13 respondents of control group. The technique of sampling for this research was simple random sampling. To analyze the data, paired sample t-test was used at α < 5%. The result of this research shows that the average of uric acid level before given intervention was 7,50mg/dl on intervention group and 7,25mg/dl on control group. The average of uric acid after given intervention was 6,60mg/dl on intervention group and 7,70mg/dl on control group. The conclusion of this research is there was the effect of ergonomic gymnastic toward the changes of uric acid on patients of uric acid p(0,000).For the researcher, it is better to do it for a longer period of time and do the measurement after the exercise is done so as to get a significant change in uric acid levelsKeyword :Uric Acid, Ergonomic Gymnastic